Metal–organic framework-based materials for photocatalytic overall water splitting: Status and prospects - Yang An; Lingling Wang; Weiyi Jiang; Xinling Lv; Guoqiang Yuan; Xinxin Hang; Huan Pang (Polyoxometalates, 2023)
With the exhaustion of conventional fossil fuels, the exploration of green and sustainable energy will become an important topic of social development. Hydrogen is considered a clean and effective energy source, and its combustion produces only water, which is harmless to the environment. Photocatalytic water splitting, which utilizes solar energy and produces H2 and O2, can become a very important reaction for alleviating energy shortages and environmental pollution. Water splitting includes the reduction and oxidation half-reactions, among which the oxidation half-reaction is the rate-determining process. Even though current studies mainly focus on the H2 or O2 evolution reactions in the presence of sacrificial agents, overall water splitting remains a challenging problem. Metal–organic frameworks (MOFs) and their precursors have been attracting increasing attention as photocatalysts for water splitting. This paper reviews the research progress in MOFs for photocatalytic overall water splitting and discusses the development prospects and challenges of MOFs. In this study, the research progress in MOF-based water-splitting catalysts for photocatalysis and electrocatalysis is systematically reviewed. Herein, MOF-based catalysts are classified into MOFs, MOF composites, and MOF-derived photocatalysts. We also analyze the prospects and challenges in the preparation of efficient and stable MOF photocatalysts for overall water splitting and propose the construction of new efficient MOFs with double active sites, aiming to improve the efficiency of photocatalytic hydrogen and oxygen evolution to achieve the overall water splitting.